TEACHING ENGLISH WITH ICT TOOLS - Azamatova, Gulrukh (MMIT Proceedings, 2023)
English, an extensively used language of today, has often been mentioned as 'global language'. It is the lingua franca of the current era and the same is taught and learnt as a second language around the world. In our country also there are given copious opportunities to learn and teach this language. We are surviving in a world where technology is omnipresent and indispensable. Owing to the ubiquitous presence of technology, the pedagogy of teaching English has also undergone a huge change. This article illustrates how ICT tools can be used in teaching ESL and promotes to ensure effective and quality teaching.